Probiotic characteristics, anti-inflammatory and anti-cancer effect of short chain fatty acid-producing Escherichia coli isolated from healthy human microbiota - Nakkarch, Atchareeya (2020)
Human intestine is a great reactor to decompose dietary fiber to short chain fatty acids (SCFA) by indigenous gut microbiota that serve as energy for their growth and as anti-inflammation agents in human gut. Therefore, this research was aimed to isolate and characterize short chain fatty acid-producing bacteria from human feces. Five gut microbiota that isolated from three healthy volunteers were identified as the highest butyric producing bacteria, which were subsequently verified for their survivability under acid and bile condition, antimicrobial activity, hemolytic activity and mucin adhesion. The selected butyric producing bacteria were identified as Escherichia coli by 16s rRNA analyses. As for the probiotic, anti-cancer and anti inflammatory characteristics, E. coli KUB-36 was identified as the most potentials probiotic bacteria among the SCFA producing E. coli strain that were isolated from human gut microbiota. The outer membrane of E. coli strain may contain the potent immunostimulatory lipopolysaccharide molecules. Hence, the toxin genes were investigated for E. coli KUB-36 and the results showed the lack of some endotoxin genes that related to LPS synthesis and absence of enterotoxin genes that related to diarrheas incidences, indicating that E. coli KUB-36 is presumptive safe bacterium. Moreover, LPS was extracted from E. coli KUB-36 has low effect to induce inflammatory cytokine on THP-1 macrophage cell line. The anti-cancer and anti inflammatory effects of E. coli KUB-36 metabolites and individual SFCA that presents in E. coli KUB-36 metabolites were further investigated by using breast and colon cancer cell lines and macrophage cell. The cytotoxicity activity showed that E. coli KUB-36 produced anti-cancer effect on both cancer cell lines, while exhibited limited cytotoxicity effect on normal cells. Moreover, amongst the SCFA that present in the metabolite of E. coli KUB-36, acetic acid demonstrated higher cytotoxicity activity. As for the anti-inflammatory activity, E. coli KUB-36 metabolites and its SCFA suppressed inflammatory cytokine and induced anti inflammatory cytokine simultaneously. In conclusion, the results in this research suggested that E. coli KUB-36 have vast potential as probiotic bacterium since it has the ability to survive under acidic and bile condition, did not possess endo- and exotoxins but exhibited favorable anticancer and anti-inflammatory effects.